ASPEK PERENCANAAN DALAM PENGELOLAAN KEUANGAN DAERAH BERDASARKAN STANDAR AKUNTANSI PEMERINTAH - -, Sutarno (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2006)
ABSTRACT The mechanism of the financial management is not mainly supported by the law of central and regional financial balance. Other supporting regulations are the law of state finance, the law of state treasury, the law of national draft, the law of anti-corruption and a particular accounting guideline (state accounting system). One of the most essential aspects of the regional finance that should be realized is the regional financial system as a part of the national financial system. Thus, every financial activity in region should refer to a particular accounting standard, i.e. state accounting standard. Keywords: regional finance, state accounting standard, traditional budget, new public management.